The Influence of Islamic Business Ethics Implementation in Building Customer Loyalty at PT. Askrindo - Khotima, Husnul; Arif, Muhammad; Inayah, Nurul (IAIN Manado, 2025)
This study aims to analyze the influence of ethical principles in Islamic business practices on customer loyalty at PT Asuransi Kredit Indonesia (Askrindo) in In Medan. The research uses a quantitative approach with a survey method involving 100 active customers as samples. The measurement tool used in this study has been tested for validity and reliability to ensure that the data collected is trustworthy and reflects the existing reality. This method was chosen because it is deemed the most suitable for measuring the relationship between the independent variable, the application of Islamic business ethics principles, and the dependent variable, customer loyalty. Moreover, this method allows data to be collected and analyzed statistically using simple linear regression. The analysis results show that the application of Islamic business ethics principles has a significant impact on customer loyalty, reflected in an R-square value of 0.562 and a significance level of 0.000. These findings indicate that the higher the application of Islamic business ethics such as honesty, trustworthiness, fairness, and responsibility, the stronger the level of trust, satisfaction, and customer loyalty towards the company. Therefore, this study recommends that PT Askrindo strengthen the application of ethics principles in its operations by increasing transparency, improving service quality, and providing Islamic business ethics training to employees in order to further maintain and enhance customer loyalty.